PUBLIC POLICY ANALYSIS: HOW MUTUAL PUBLIC RELATIONS SUPPORT EQUITABLE ACCESS TO EDUCATION - khoiroh, Ummul; Ade, Moses; Noorhayati, Siti Mahmudah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to analyze the role of Mutual Public Relations (MPR) in supporting public policy to increase equal access to education. Using a qualitative approach through case studies at SMPI Al-Ilzamy, this research reveals the application of MPR as a communication strategy to disseminate information, involve parents, and support educational policies such as scholarship programs and academic assistance. The research results show that the MPR functions not only as an information channel but also as a liaison between schools and the community through two-way communication, which allows parents and students to provide input and understand policies better. This research emphasizes the importance of the MPR as an effective strategy for creating active community involvement and supporting equitable access to inclusive and fair education